Elevation influence the macrofungi diversity and composition of Gunung Korbu, Perak, Malaysia - Aqilah Bakray; S. NURJANNAH; S. SALLEH; B.K. THI; Z. AHMAD FITRI; M. MOHD KHAIRUL FAIZI; K.M. HAJA MAIDEEN; M.S. NIZAM (Society for Indonesian Biodiversity, 2020)
Abstract. Nur ‘Aqilah MB, NurJannah S, Salleh S, Thi BK, Ahmad Fitri Z, Mohd Khairul Faizi M, Haja Maideen KM, Nizam MS. 2020. Title. Biodiversitas 21: 1707-1713. Fructification of macrofungi depends on two main factors, abiotic and biotic. In this study, the main focus is to determine the macrofungi composition and diversity as the effect of elevation and substrate. Macrofungi collection was conducted at three different elevations along the trails (Trail A, B, and C) of Gunung Korbu in July 2019. The sampling area was divided by ascent elevation from the Seroja Camp to the Rimba Gate (Trail A, 796 m above sea level[a.s.l]), the Seroja Camp to the Kijang Camp (Trail B, 1092 m a.s.l) and the Kijang Camp to the summit of Gunung Korbu (Trail C, 2183 m a.s.l). The collected macrofungi were photographed, described based on their macroscopic characters and any colour changes when bruising or chemicals reactions were recorded. In total 90 macrofungi specimens were in good condition belonging to 6 families from 13 genera, including the unidentified. About 93.33% (84 specimens) of the collections are saprotrophic fungi and six parasitic fungi. Trail B recorded the highest diversity index of 2.20 and 0.87 for Shannon Index and Simpson index, respectively. Non-metric multidimensional scaling ordinations showed a clear separation pattern of macrofungi community found in three different trails, with most of the specimens found in Trail B.